1999
DOI: 10.1136/vr.144.12.315
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic mitral valve prolapse in cavalier King Charles spaniels: epidemiology and prognostic significance for regurgitation

Abstract: This study investigated the epidemiology and prognostic significance of mitral valve prolapse, detected by ultrasonography, in 153 cavalier King Charles spaniels which were screened consecutively during a period of one year. Seventy-five of the dogs, which had either no murmur or a grade I murmur on screening, were reexamined three years later. The screening revealed that 82 per cent of the dogs aged one to three years and 97 per cent of the dogs over three years had various degrees of mitral valve prolapse. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 19 publications
10
102
3
1
Order By: Relevance
“…As the nodules grow, they can fuse and lead to generalized thickening of the mitral valve [7,8]. Moreover, elongation of the leaflets and stretching of the chordae tendineae are usually observed, leading to valvular leaflet prolapse in the left atrium (LA) [9]. The chordae tendineae can rupture, depriving the valve of its support and further aggravating the leakage [10].…”
Section: D and Tm Echocardiographic Features Of Dmvd Mitral Valve Anmentioning
confidence: 99%
“…As the nodules grow, they can fuse and lead to generalized thickening of the mitral valve [7,8]. Moreover, elongation of the leaflets and stretching of the chordae tendineae are usually observed, leading to valvular leaflet prolapse in the left atrium (LA) [9]. The chordae tendineae can rupture, depriving the valve of its support and further aggravating the leakage [10].…”
Section: D and Tm Echocardiographic Features Of Dmvd Mitral Valve Anmentioning
confidence: 99%
“…The murmur is a hallmark of the disease and can be found in middle-aged to aged dogs, although Cavalier King Charles Spaniels (CKCS) can be affected as early as from one to two years of age (7). Cavalier King Charles Spaniels seem also to have a higher prevalence of MMVD in comparison to other breeds (8).…”
Section: Natural History Of the Diseasementioning
confidence: 99%
“…A stronger right-thanleft apical-murmur had a positive predictive value (PPV) of 83% and was 96% specific for TR≥35 mmHg; when combined with syncope, it had a PPV of 92% and was 92% specific (10). Pedersen's study revealed that 82% of CKCSs aged one to three years and 97% of dogs aged more than three years had various degrees of mitral valve prolapse, which is one of the predisposition factors for MMVD (7). Other factors that may contribute to the disease are physical, physiological and other types of stress.…”
Section: Natural History Of the Diseasementioning
confidence: 99%
“…Thickening and prolapse of the mitral valve are also suggested to be included in the echocardiographic parameters to diagnose chronic mitral valve disease in dogs (Pedersen et al, 1999b;Olsen et al, 2003). However, early, mild cases might show equivocal or no alterations which might be the reason while we had these signs only in one of our dogs (Terzo et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…at least with mild mitral insufficiency). Pedersen et al (1999b) detected a systolic, left apical (mitral valve) murmur in 45/153 (29%) Cavalier King Charles Spaniels between one and 10 years of age and being free of any other clinical signs of cardiovascular diseases but they did not report the number of these dogs with regard to Doppler echocardiographic findings. Trafny et al (2012) have recently reported the occurrence of mitral valve disease in 23 (48%) out of 48 overtly healthy, more than 6 years old Norfolk Terriers with the presence of a systolic, left apical, i.e.…”
Section: Discussionmentioning
confidence: 95%